Impact of different polishing techniques on surface roughness, gloss, and microhardness of zirconium oxide reinforced flowable bulk-fill resin composite: an in vitro study - Amr Elsayed Elnahas; Mohamed Elshirbeny Elawsya; Abeer ElSayed ElEmbaby (BMC Oral Health)
Abstract Background To evaluate the impact of different polishing systems on surface roughness (SR), surface gloss (SG), and vickers microhardness (VMH) of flowable bulk-fill composites reinforced with zirconium oxide fillers. Methods Two flowable bulk-fill composites reinforced with zirconium oxide fillers (PALFIQUE BULK FLOW, Filtek Bulk Fill Flowable) and another one with conventional fillers (Tetric N-Flow Bulk Fill) were used. For each tested material, 40 cylindrical specimens (8-mm diameter, 4-mm height) were prepared. Specimens were divided into 4 subgroups according to polishing system used (n = 10/subgroup): subgroup I; Mylar strip (control), subgroup II; 1-step polishing system, subgroup III; 2-step polishing system, and subgroup IV; multi-step polishing system. Surface roughness was evaluated with a 3D noncontact optical profilometer. Gloss was evaluated with a glossmeter. Microhardness was evaluated with a Vickers Microhardness tester. Statistical analysis was performed using two-way ANOVA, Bonferroni, and Pearson correlation coefficient testes (p < 0.05). Results For surface roughness, there was no significant difference between groups for control and 1-step (p = 0.152 for control, p = 0.296 for 1-step), while there was a significant difference for 2-step and multi-step (p = 0.025 for 2-step, p = 0.001 for multi-step). For gloss, there was no significant difference between groups for 1-step and 2-step (p = 0.124 for 1-step, p = 0.226 for 2-step), while there was a significant difference for control and multi-step (p = 0.001 for control, p < 0.001 for multi-step). For microhardness, there was no significant difference between groups for control (p = 0.245), while there was a significant difference for the other techniques (p < 0.001 for 1-step and 2-step, p = 0.001 for multi-step). Conclusions Reinforcement with zirconium oxide fillers improved flowable bulk-fill composites in terms of surface roughness, gloss, and microhardness. Surface gloss and microhardness were significantly influenced by material type and polishing system used, while surface roughness was influenced only by polishing system used.